Preparation and characterization of Ag–Pd bimetallic nano-catalysts in thermosensitive microgel nano-reactor. Issue 33 (18th May 2018) - Zhang, Tao; Li, Li; Ye, Zhishuang; Yang, Qingsong; Tian, Yuchuan; Guo, Xuhong
Abstract : Thermosensitive microgels with PS core and cross-linked PNIPA shell were synthesized as nano-reactor to prepare Ag–Pd bimetallic nanoparticles. Abstract : Thermosensitive microgels consisting of a solid core of polystyrene and a shell of cross-linked poly( N -isopropylacrylamide) (PNIPA) were synthesized as nano-reactors, in which Ag–Pd bimetallic nanoparticles were prepared through simultaneous in situ reduction reaction. The spatial distribution of metallic nanoparticles in the microgels was analyzed by small angle X-ray scattering (SAXS) and the results indicated that metal nanoparticles were mainly located in the inner layer of microgels. The catalytic activity of Ag–Pd bimetallic nanoparticles was investigated using the reduction of p -nitrophenol to p -aminophenol by NaBH4 as model reaction. The data demonstrated that Ag–Pd bimetallic nanoparticles showed enhanced catalytic activity compared to each monometallic nanoparticle alone and their catalytic activity was controllable by temperature due to the volume transition of PNIPA microgels.